PERANAN OLAHRAGA TERHADAP KAPASITAS KARDIORESPIRASI - Lismadiana Lismadiana (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
Increased age resulted in a decline in the ability of a person physically and physiologically . Someone quickly look old or younger seem fast or slow depending on the physical condition and mental deterioration . The decrease in the ability to take place sooner or later all influenced by physical activity performed.The decrease in functional capacity of the human body organs one due to declining cardiorespiratory endurance as a result of reduced cardiac function and lung is a vital organ to drive the entire system is contained within the human body .Physical activity ( exercise ) greatly affect the maintenance of the capacity of the organs physiology (function ) of the body . By doing regular exercise will result in (1). Increasing the size of the heart , (2) The reduced pulse rate, (3) . Increased stroke volume ( stroke volume ), (4) . Increased blood volume and hemoglobin , (5) . Changes in capillary density and muscle hypertrophy . While changes in the reputation system are: ( 1 ) . The increase in maximal minute ventilation , (2) . Increased efficiency ventilatori , (3) . The increase in the volume of various kinds of lung , (4) . Increased diffusion capacity . Key words : physical activity ( exercise ), regularly , cardiorespiratory capacity